ANALYSIS OF PREVALENCY, INTENSITY, AND CORELATION OF PARASITE WITH ENVIRONMENTAL CONDITIONS IN MILKFISH (Chanos chanos) IN TRADITIONAL POLYCULTURE PONDS OF KEDANYANG VILLAGE - Mohammad Yusuf Atsnani; Farikhah (Hasanuddin University, 2023)
This study aimed to examine the relationship between parasite prevalence in milkfish and water quality in the Traditional Fishponds of Kedanyang Village, Gresik Regency. The research was conducted for one month in April 2023. Random samples of milkfish were taken from two ponds, with a total of 40 fish. Parasite examination was performed by observing ectoparasites on mucus, gills, fins, and scales, as well as endoparasites in the fish's internal organs. The identification results revealed the presence of two types of parasites in the traditional polyculture ponds of Kedanyang Village, namely Dactylogyrus found in the gills and Cappilaria sp. found in the digestive tract. The prevalence and intensity of these parasites ranged from 2.5% to 5% and 1-2, respectively, which can be classified as low. The water quality in the ponds was categorized as good and well-tolerated by the fish. Correlation analysis showed that temperature, salinity, ammonia, nitrite, and nitrate had a weak positive relationship with parasite prevalence, while pH, dissolved oxygen (DO), and biochemical oxygen demand (BOD) had a weak negative relationship.